Young house love : 243 ways to paint, craft, update & show your home some love - Petersik, Sherry. frey50; Petersik, John. (New York : Artisan, 2012)
This debut book by bloggers Sherry and John Petersik is filled with hundreds of fun, deceptively simple, budget-friendly ideas for sprucing up a home.
The young house love manifesto -- Decorating is a journey, not a destination -- Guys can pick out pillows and gals can swing a sledgehammer -- Decorating rules are meant to be broken! -- If we can do it, anyone can. seriously -- Rome wasn't built in a day -- and it probably wasn't decorated in a day either -- You learn as much from your mistakes as your successes -- Don't look at a glossy picture and think "My house will never look like that" -- think "OK ... where can I start?" -- Relax, it's only decorating.
Keywords: Petersik, Sherry -- Homes and haunts; Petersik, John -- Homes and haunts; Dwellings -- Remodeling; Interior decoration; Housekeeping; Dwellings -- Maintenance and repair